(3JMQjQ GdeLSWis - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3HWdjehS GdMcje GdbdhPjs ((3YHO GdcGai Hf YHO GdeLjO Hf YHjO Gddg GdJHQjRi s)
(3ChdgG (B:s
(3HYO GdOjHGLI abO cfJ HQgg ef GdReGf YGRakG Ydi Cf CMQQ dfaSi hdSGFQ WdHI GdYde ef GdENhGf GdeLSWi GdefShH Edi HWdjehS GdbhOi s
(3BNQgG (B:s
(3hEPG CJeefG LejY eGfU EdiEQTGOg ef hLhO eG jMJGL Edi hLhO hJUMjM eG jMJGL Edi JUMjMg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B160 - (3U(B180s
(3JMJhi Ydi cKjQ ef GdLOGhd hGdQShe GdgfOSjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B511 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B15 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs